2010
DOI: 10.1108/13552541011025843
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterisation of PA‐Al2O3 composites obtained by selective laser sintering

Abstract: PurposeThis paper aims to develop a deep characterization of PA‐Al2O3 composite for selective laser sintering (SLS). Tension test is used to determine main mechanical characteristics of the material, both at room temperature and at 100°C. An accurate knowledge of the parts' performances as a function of the building orientation, is fundamental to understand the manufacturing anisotropy. Particular attention is dedicated to the joining and failure micromechanisms ruling the macroscopic characteristics, on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 10 publications
(8 reference statements)
3
18
0
Order By: Relevance
“…Similar conclusions related to anisotropy in the growth direction (z axis) are observed in the research carried out by Berti et al (2010) applied to PA-Al2O3 composite for selective laser sintering (SLS) and in the work carried out by E. Bassoli et al (2012) in the case of metal or ceramic filler. In conclusion either the design or the material of SLS part has to be changed if this technology is wanted to be used for this kind of clutch pedal.…”
Section: Results Of Preliminary Worksupporting
confidence: 67%
“…Similar conclusions related to anisotropy in the growth direction (z axis) are observed in the research carried out by Berti et al (2010) applied to PA-Al2O3 composite for selective laser sintering (SLS) and in the work carried out by E. Bassoli et al (2012) in the case of metal or ceramic filler. In conclusion either the design or the material of SLS part has to be changed if this technology is wanted to be used for this kind of clutch pedal.…”
Section: Results Of Preliminary Worksupporting
confidence: 67%
“…Polyamide (PA) specimens manufactured by SLS; three different configurations were manufactured with the purpose of evaluating the effect of building direction on Mode I fracture mechanic properties of the material. Similar studies on PA-Al2O3 composites have been presented by [5,6], mainly focused on tensile or bending properties. The novelty of this work lays in its focus on the fracture mechanics properties of PA for SLS, and on the investigation on the capability of AM processes to build 3D artificial cracks, otherwise impossible to create by classic methods.…”
Section: Introductionmentioning
confidence: 83%
“…[4] performed a rigorous analysis of the Young's modulus, ultimate tensile strength, and strain-to-failure of a glassfilled nylon PA12 composite called DuraForm®, demonstrating the variability of the material properties throughout the built volume and between builds. Berti et al [5] also tensile tested specimens built with different orientations, at two different temperatures. They found that the most important anisotropy is located between the vertical direction and the horizontal plane, but near the upper operative temperature the mechanical difference between specimens built with longitudinal axis parallel to the two horizontal directions becomes important.…”
Section: Introductionmentioning
confidence: 99%
“…It offers high throughput, no need for supports except from the first layers to be detached from the machine worktable, no post-processing, wide range of materials, high automation possibilities (Eyers and Dotchev, 2010;Bassoli et al, 2005;Caulfield et al, 2007). Fully functional components can be obtained for example in polyamide (unfilled or reinforced with glass fibres/beads, Aluminium and carbon), flame retardant polyamides and Polyetheretherketone (PEEK) for automotive, aerospace and military industries, but also biomedical devices and consumer goods (Eyers and Dotchev, 2010;Berti et al, 2010;Senthilkumaran et al, 2009). Polyamide-matrix composite parts can be produced directly from the CAD model, without any post-treatment.…”
Section: Introductionmentioning
confidence: 99%